Impact of the COVID-19 pandemic on the functioning of selected tourist attractions in Poland - Kruczek, Zygmunt; Nowak, Karolina (Turystyka w badaniach podstawowych, 2023)
The article, based on the monitoring of attendance at selected tourist attractions conducted by the authors, presents data on the functioning of attractions during the COVID-19 pandemic and in the period of recovery from the pandemic crisis. Changes in the scale and type of tourist and the creation of online substitutes for sightseeing, as well as stimulating attendance at attractions through tourist vouchers, were pointed out.